Factors Affecting Academic Performance and Motivation among Holy Cross College Sta. Rosa Grade 12 Students - Cordova, Missy S.; Maria, Jercie Mae Sta.; Santos, John Vincent Llenada (STAI Miftahul Ula Nganjuk, 2022)
The goal of this study was to identify the elements that contribute to students' academic performance and motivation in Grade 12 Senior High School. The components are divided into five categories: learning skills, parental background, peer influence, teacher quality, and learning infrastructure. To quantitatively assess and analyze the factors, the researcher employed a descriptive-correlational study approach. The findings indicate that respondents descriptively agree on all factors while demonstrating a substantial association with performance and motivation, revealing that the enumerated factors indeed influence performance and motivation.